Hubungan Pengetahuan Anak Dengan karies Gigi Anak Kelas VA SDI Raden Paku Surabaya Tahun 2020 - Josinta Elsiana Maryanti Tameon (Jurnal Skala Kesehatan, 2021)
Abstract: Frequent oral and dental diseases in Indonesia are tooth caries and high in number. Elementary school age (SD) is one of the children's age groups that are susceptible to tooth caries. A child's knowledge of dental caries is so important that it can increase the degree of dental health and the mouth of tooth caries. The purpose of this study is to identify the relationship of a child's knowledge with child's gear caries and data collection techniques using the knowledge questionnaire and the knowledge karies observation sheet and the data analysis techniques using the chi square test. The study employed a quantitative method with a design for cross sectional. This research sample is an elementary class of VA SDI Raden Paku Surabaya is 52 children. Research shows that the child's knowledge of teeth and mouth karies is largely in the good category of answering 15-22 questions of 35 children (67.2%), the most teeth karies of teeth are found at criteria >1 are in a bad category with 39 children's dental caries (75%), and thus it appears that there is no link between a child's knowledge and a child's dental caries which are proved by significant value (0.942 sig > 0.05). In conclusion, a child's knowledge of good tooth karies does not affect the tooth karies of a child. Keyword : Caries teeth, Knowledge, Students